First record of three fish species in Río Grande de San Ramón, Costa Rica (UNED Research Journal, 2019)
Four sampling trips (2016 and 2017) in Río Grande de San Ramón (Tárcoles River Basin, 1 060masl) produced nine species, three of them for the first time for this altitude or basin. Previously, Alfaro cultratus (N=95) was reported only up to 300masl at the Caribbean slope and in the Tempisque River basin; Amatitlania siquia (N=4) only under 540masl for the Tárcoles river basin; and Amatitlania septemfasciata (N=22) from the Atlantic slope and below 600 masl.
Keywords: distribution area; freshwater; fishes; Alfaro cultratus; Amatitlania siquia; Amatitlania